2016
DOI: 10.3390/ijms17091397
|View full text |Cite
|
Sign up to set email alerts
|

Calcium-Sensing Receptor in Human Peripheral Blood T Lymphocytes Is Involved in the AMI Onset and Progression through the NF-κB Signaling Pathway

Abstract: Acute myocardial infarction (AMI) is a condition triggered by an inflammatory process that seriously affects human health. Calcium-sensing receptor (CaSR) in T lymphocytes is involved during the inflammation reaction. However, the relationship between them is not very clear. In this study, we collected human peripheral blood T lymphocytes from patients with AMI and in different stages of percutaneous coronary intervention (PCI) (at the onset of AMI, the first day after PCI (PCI-1), PCI-3, and PCI-5) to study t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 26 publications
2
15
0
Order By: Relevance
“…It was also found that, no matter how U0126 or SP600125 changed, the degree of cytokine release was lower, compared with that induced by the positive CaSR siRNA plasmid. These results were consistent with our previous results (13). Therefore, the activation of CaSR had a specific effect, not only through the NF-κB pathway, but also through partial MAPK pathways.…”
Section: Levels Of Ldh Mda and Sod Released By Cardiomyocytessupporting
confidence: 94%
See 4 more Smart Citations
“…It was also found that, no matter how U0126 or SP600125 changed, the degree of cytokine release was lower, compared with that induced by the positive CaSR siRNA plasmid. These results were consistent with our previous results (13). Therefore, the activation of CaSR had a specific effect, not only through the NF-κB pathway, but also through partial MAPK pathways.…”
Section: Levels Of Ldh Mda and Sod Released By Cardiomyocytessupporting
confidence: 94%
“…The previous study also revealed that the activation of CaSR was involved in cardiac ischemia-reperfusion (I/R) injury and that it may promote ventricular cardiomyocyte apoptosis in neonatal rats through activating the MAPK signaling pathway (12). In another of our previous studies, it was confirmed that the activation of CaSR in T lymphocytes regulated cell physiological function through NF-κB signaling pathways in AMI and percutaneous coronary intervention (PCI) postoperative processes (13). In the experiment, it was found that CaSR small interfering RNA (siRNA)-positive plasmid-transfected T lymphocytes and the NF-κB pathway inhibitor Bay-11-7082 decreased the level of phosphorylated (P-) p65 in AMI.…”
Section: Calcium-sensing Receptors In Human Peripheral T Lymphocytes mentioning
confidence: 77%
See 3 more Smart Citations